An Improved GaN-Based Light-Emitting Diode with a SiO2 Current Blocking Layer Embedded in Stair-Like AZO Transparent Structure. (29th September 2017) - Liou, Syuan-Hao; Tsai, Jung-Hui; Liu, Wen-Chau; Lin, Pao-Sheng; Chen, Yu-Chi
Abstract : In this article, in order to enhance the optical characteristics, GaN-based light-emitting diodes (LEDs) with SiO2 current blocking layer and stair-like aluminum-doped zinc oxide (AZO) transparent layers are fabricated and demonstrated. The characteristics of the LEDs with a planner AZO transparent layer, a SiO2 current blocking layer embedded in planner AZO transparent layer and a stair-like AZO transparent structure, and a SiO2 current blocking layer embedded in stair-like AZO transparent structure are comparatively studied. Experimental results exhibit that the current crowding effect can be effectively improved and it shows the best optical characteristics for the use of a SiO2 current blocking layer embedded in the stair-like transparent structure. At current level of 20 mA, it exhibits the improvements by 17.37%, 37.9%, and 26.3% in light output power, external extraction efficiency, and wall-plug efficiency, as compared to the conventional device with a planner transparent layer.